Effects of pioglitazone on cognitive function in patients with a recent ischaemic stroke or TIA: a report from the IRIS trial. Issue 1 (22nd September 2017) - Furie, Karen L; Viscoli, Catherine M; Gorman, Mark; Ford, Gary A; Young, Lawrence H; Inzucchi, Silvio E; Guarino, Peter D; Lovejoy, Anne M; Conwit, Robin; Tanne, David; Kernan, Walter N
Abstract : Introduction: Patients with cerebrovascular disease are at increased risk for cognitive dysfunction. Modification of vascular risk factors, including insulin resistance, could improve poststroke cognitive function. Methods: In the Insulin Resistance Intervention after Stroke (IRIS) trial, patients with a recent ischaemic stroke or transient ischaemic attack (TIA) were randomised to pioglitazone (target 45 mg daily) or placebo. All patients were insulin resistant based on a Homeostasis Model Assessment-Insulin Resistance score >3.0. For this preplanned analysis of cognitive function, we examined the Modified Mini-Mental State Examination (3MS) score (maximum score, 100) during follow-up. Patients were tested at baseline and annually for up to 5 years. Longitudinal mixed model methods were used to compare changes in the 3MS over time. Results: Of the 3876 IRIS participants, 3398 had a 3MS score at baseline and at least once during follow-up and were included in the analysis. Median 3MS score at baseline was 97 (IQR 93–99). The average overall least squared mean 3MS score increased by 0.27 in the pioglitazone group and by 0.29 in the placebo group (mean difference between treatment groups −0.02; 95% CI −0.33 to 0.28, p=0.88). Conclusions: Among insulin-resistant patients with a recent ischaemic stroke or TIA, pioglitazone did not affect cognitive function, as measured by the 3MS, over 5 years. Trial registration: ClinicalTrials.gov NCT00091949 ; Results.